ECOLOGICAL AND ECONOMIC SECURITY OF THE AGRICULTURAL SECTOR - PІSHСHЕNKО Oleg (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article examines the ecological and economic security of the agricultural sector. Achieving global food security and food security requires a global approach to food systems. It was found that there is a significant relationship between agriculture and the environment. Sustainable agricultural development ensures food quality and, in tandem, prevents natural disasters such as droughts. However, to meet the food needs of a growing population, poor quality laws and unacceptable agricultural practices arise, which in turn leads to environmental degradation. To meet the food needs of the world’s population, the agricultural sector has been subjected to huge loads and created emissions. Sustainable agriculture helps increase food production while reducing the use of pesticides. It has also been observed that agricultural production sometimes accumulates carbon, thus polluting the environment. It has been shown that there is a significant link between economic growth and environmental pollution. On the other hand, pollution reduction and environmental balance are not sufficiently prioritized in developing and underdeveloped countries